Sociological Analysis of the Factors Influencing the Voting Pattern - karim rezadoust; marziyeh shahriari; mona fazelipour (توسعه اجتماعی, 2018)
Public participation in the development process of the decision to run the most effective way to achieve sustainable development. The voting pattern indicates a certain type of political behavior that is based on a set of norms, attitudes and attitudes of a society. His aim of this study was to analyze the sociological factors influencing the voting pattern of the martyr Chamran University is. The research methodology used in collecting and analyzing data survey, using random sampling was conducted on 150 university professors martyr Chamran is that its reliability, validity and reliability using alpha statistic method Alpha is measured. In analyzing the data, descriptive statistics such as mean and frequency distribution tables and analytical methods, such as correlation and linear and logistic regression analysis were used. Based on the findings of the study, a significant correlation between the size of the pattern of voting and political dimensions of social networking and socialization there.